A Study On Malay Apostates In Malaysia - Nalathamby, Santhira Mogan (2021)
Muslims in Malaysia were shaken about four years ago with news that so many Malays have converted to Christianity, resulting in a show of open animosity towards Christians and anyone who leaves Islam. The objectives of this research are to evaluate the position of apostasy in Islam, to examine the legal position of apostates in Malaysia and analyse their demographics